Picking on the new kid: Firm newness and deception in buyer–supplier negotiations. Issue 1 (January 2020) - Rottenburger, Jörg R.; Kaufmann, Lutz
Abstract: This study builds on liabilities of newness theory and moral disengagement theory to investigate deceptive behavior in buyer–supplier negotiations that involve new ventures. Using two purchasing negotiation experiments, it contrasts how negotiators treat employees of new ventures, mature firms, and firms of unknown age. The first experiment examined the behavior of participants in their role as salespeople toward buyers, whereas the second one examined the behavior of participants in their role as buyers toward salespeople. Across experiments, participants shared the belief that their negotiation counterparts were less experienced when these counterparts worked for new ventures than when they worked for mature firms. Moreover, both groups were more likely to deceive negotiation counterparts working at new ventures, although this effect was stronger in magnitude in the first experiment. These findings contribute to the field of behavioral supply management by identifying a new situational variable (firm newness) that promotes deception in purchasing negotiations. Moreover, they provide implications for buyers and suppliers on how to leverage preconceptions associated with their firm's age to gain advantages (or avoid disadvantages) in buyer–supplier negotiations. Finally, we add to liabilities of newness theory by identifying an additional liability that affects new ventures – namely, the increased risk of being deceived. Highlights: Combines & advances research on supply management, entrepreneurship, and psychology. A scenario-based approach mimics an online, buyer–supplier negotiation. Findings show suppliers to assume buyers in new ventures as relatively inexperienced. In B2B negotiations, new ventures are more likely to be deceived than mature firms.